Ethical Dilemma: Is it Worthwhile Operating an End-Stage Pancreatic Cancer Patient with Acute Mesenteric Artery Ischemia? - Damaskos, Christos; Garmpis, Nikolaos; Garmpi, Anna; Georgakopoulou, Vasiliki Epameinondas; Patsouras, Alexandros; Sypsa, Georgia; Syllaios, Athanasios; Antoniou, Efstathios A. (Acta medica Lituanica, 2021)
Pancreatic cancer is as an aggressive malignancy with low survival rates. We present the first case of an operation of acute mesenteric ischemia performed in a patient with end-stage pancreatic adenocarcinoma. Through this case, we also discuss raising concerns regarding the management of severe complications such as acute mesenteric ischemia in patients with progressed pancreatic carcinoma. How ethical is to leave patients untreated? The decisions for management of patients with advanced disease are strongly based on the expected quality of life, ethical principles, different religions and spiritualities, and the burden of healthcare cost.
Keywords: End-stage pancreatic cancer; Acute mesenteric artery ischemia; Surgery; Treatment; Ethical dilemma